Strategi Menanamkan Pendidikan Akhlak di Era Disrupsi - Ofi Afiatun Hindun Ulfah; Layla Mardliyah; Iis Sugiarti (Jurnal Kependidikan, 2022)
The development of science and technology is an incredible achievement of mankind. Namun in this era of progress has led mankind to face various increasingly complex problems, including the fading of the morals of the younger generation. This article intends to analyze moral education strategies in the era of disruption. The type of research in this study is qualitative by using the pustaka study method. The results of this study show that strengthening moral education in this disruptive era is the main need of the world of education, to form a superior, cultured and civilized generation of the nation. The strategies that can be carried out to strengthen moral education in his delivery are: it is necessary to introduce a complete and comprehensive understanding of the concept of morals itself; carry out integrative-inclusive moral education; carry out habituation strategies (conditioning), provide understanding (insight), and exemplary (modelling); implementing sufistic approach methods to overcome moral crises; and disseminating how to use digital media wisely.